Community Changes in Pregnancy Services during the Covid-19 Pandemic - Sri Hilmi Pujihartati; Argyo Demartoto (Indonesian Association for Public Administration (IAPA), 2021)
This article will discuss how to adjust and the condition of services in health facilities, especially for pregnant women during the pandemic. The method used is literature study to obtain data and finally it will be condensed into a conclusion. The theory of behavior change is the basis for analyzing changes in community behavior in health services during the Covid- 19 pandemic. The purpose of this paper is to provide an understanding of how the actual situation in society, especially in the health sector of pregnant women during the Covid-19 pandemic is. The results showed that in the health sector there were considerable changes. This change is not only carried out by medical personnel, but also needs to be balanced by public awareness. Due to this pandemic, people must pay more attention to themselves, especially for pregnant women. For pregnant women, it can be done through online examinations and consultations with medical personnel or face to face with strict health protocols. In addition, monitoring can also be carried out independently from home by referring to the MCH handbook. Understanding and knowledge of pregnant women is needed in addition to reducing the intensity of pregnancy checks. For this reason, pregnant women need to behave in a healthy way by referring to the policies issued by the Indonesian Ministry of Health. Optimizing the health of pregnant women is very much needed in reducing the incidence of Covid-19 and reducing maternal anxiety during the Covid-19 pandemic.